Second allogeneic hematopoietic cell transplantation for graft failure: Poor outcomes for neutropenic graft failure. Issue 10 (October 2015) - Lund, Troy C.; Liegel, Jessica; Bejanyan, Nelli; Orchard, Paul J.; Cao, Qing; Tolar, Jakub; Brunstein, Claudio; Wagner, John E.; Verneris, Michael R.; Weisdorf, Daniel
<x xml:space="preserve">Abstract</x> Graft failure (GF) after hematopoietic cell transplant (HCT) occurs in 5–30% of patients. GF can be accompanied by neutropenia (NGF) or can result with adequate neutrophils, but loss of donor chimerism (non‐neutropenic graft failure, NNGF). In this report, we describe the outcomes of 95 patients treated with a second HCT for GF at the University of Minnesota; 62 with NGF and 33 with NNGF. The cumulative incidence of neutrophil recovery at 42 days after second HCT was 45% for NGF and 88% for NNGF. A second GF occurred in 34 NGF (55%) and in 9 NNGF (27%) patients. The incidence of Grade III–IV acute graft versus host disease (GVHD) was 8% (95% confidence interval (CI), 1–16%) and 12% (95% CI, 1–23%) for NGF and NNGF, respectively. From the 2nd HCT, 1‐year overall survival (OS) was 44% (95% CI, 34–54%), [NNGF: 76% (95% CI, 57–87%) and NGF: 27% (95% CI, 17–39%)]. The most common cause of death after second HCT was infection (52%). In summary, the outcomes of second HCT after NGF and NNGF are different with much worse outcomes for NGF necessitating new approaches for this complication. Am. J. Hematol. 90:892–896, 2015. © 2015 Wiley Periodicals, Inc.